EFFECT OF ESSENTIAL OIL OF GRAPE (CITRUS PARADISI) PEEL ON THE SHELF LIFE AND PACKAGING MATERIALS ON SMOKED CATFISH (CLARIAS GARIUPINUS) - Olaifa, Oladayo Peter; Ogundana, Odunayo Seyi; Ojo, Babatunde Samson; Hassan, Sakirat Romoke; Olatunbosun, Rabiu Oladayo (FUDMA JOURNAL OF SCIENCES, 2025)
The essential oil derived from grapefruit (Citrus paradisi) presents a viable alternative to synthetic preservatives in food products. A study was conducted over eight weeks to assess the antimicrobial properties of this essential oil, as well as its effectiveness when used with packaging materials, specifically regarding the shelf life of smoked catfish (Clarias gariepinus). The results indicated that smoked fish coated with grapefruit peel essential oil began to show signs of spoilage after six weeks, whereas the uncoated fish exhibited spoilage after just four weeks. It was noted that the combination of grapefruit peel essential oil and ambient packaging provided the most significant protection against microbial decomposition of the fish. These findings suggest that grapefruit essential oil can effectively extend the shelf life of smoked catfish (Clarias gariepinus) when stored in ambient conditions.
Keywords: Essential oil; Catfish; Smoking; Processing; Preservation